Analysis Of Islamic Bank Influence On Agricultural Financing Sector Period 2014-2016 (Journal of Islamic Economic Laws, 2019)
One main problem that Indonesia’s agricultural sector faces is limited financial acces. This research tries to analyze  Islamic Banking influence on agricultural financing sector in Indonesia. It utilizes monthly data of Islamic banking statistic from January 2014 until December 2016. This study conducts OLS (Ordinary Least Squares) as its analytical method to intrepret the data analysis. The finding of this paper shows that the incentive of Islamic Bank Indonesia Certificate (SBIS), third party fund, inflation, Non Performing Financing influence agricultural financing significantly. But, interest rate is not affecting agricultural financing. This research suggests the increase in agricultural financing proportion for agriculture should be in accordance with increase in total deposit value. This finding recommends improvement of the human resources competency in agriculture sector as well as strengthening instruments of Islamic financing policy.